Joseph Conrad in Slovene translations - Majda Šavle (Acta Neophilologica, 2005)
Joseph Conrad gained public admiration for the romantic glamour and atmosphere of his tales of the sea, of distant coasts and exotic locales, while his fellow artists and literary critics praised his superb use oflanguage, his writing style, and his narrative techniques. The following chronological account oftranslations and critical responses to them and of the discussions about the life and work of Joseph Conrad show, that in Slovenia, too, Conrad is considered to be one of the greatest  novelists in the English language.